(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Dalit literature expresses in a caste-driven society the oppressions and exploitations faced by Dalits. As a political method of writing, Dalit writing tracks Dalits’ cultural and social existence, and politically writing calls for rebellion. Bama is a Tamil Christian Dalit writer who writes in Tamil Nadu about the lives of Dalit people. This paper looks at Bama ’s novel Sangathi as a place that portrays Dalit people and analyses how castes and gender function as instruments of dual injustice in their lives. This crucial feminist reading of the novel from a Dalit Feminist viewpoint reflects on how women are oppressed in the Paraiya group in their ties with various social structures like schooling, marriages, electoral politics etc. At the same time, we see how this text creates resistance to the injustice women experience in their daily lives in its shape and theme.